Rock outcrop orchids reveal the genetic connectivity and diversity of inselbergs of northeastern Brazil - Pinheiro, Fbio; Cozzolino, Salvatore; Draper, David; Barros, Fabio de; Felix, Leonardo P.; Fay, Michael F.; Palma-Silva, Clarisse [UNESP] (Biomed Central Ltd., 2014)
Background: Because of their fragmented nature, inselberg species are interesting biological models for studying the genetic consequences of disjoint populations. Inselbergs are commonly compared with oceanic islands, as most of them display a marked ecological isolation from the surrounding area. The isolation of these rock outcrops is reflected in the high number of recorded endemic species and the strong floristic differences between individual inselbergs and adjacent habitats. We examined the genetic connectivity of orchids Epidendrum cinnabarinum and E. secundum adapted to Neotropical inselbergs of northeastern Brazil. Our goals were to identify major genetic divergences or disjunctions across the range of the species and to investigate potential demographic and evolutionary mechanisms leading to lineage divergence in Neotropical mountain ecosystems.Results: Based on plastid markers, high genetic differentiation was found for E. cinnabarinum (F-ST = 0.644) and E. secundum (F-ST = 0.636). Haplotypes were not geographically structured in either taxon, suggesting that restricted gene flow and genetic drift may be significant factors influencing the diversification of these inselberg populations. Moreover, strong differentiation was found between populations over short spatial scales, indicating substantial periods of isolation among populations. For E. secundum, nuclear markers indicated higher gene flow by pollen than by seeds.Conclusions: The comparative approach adopted in this study contributed to the elucidation of patterns in both species. Our results confirm the ancient and highly isolated nature of inselberg populations. Both species showed similar patterns of genetic diversity and structure, highlighting the importance of seed-restricted gene flow and genetic drift as drivers of plant diversification in terrestrial islands such as inselbergs.
Keywords: Brazilian Atlantic Forest; Caatinga; Chloroplast microsatellites; Epidendrum cinnabarinum; Epidendrum secundum; Genetic drift; Nuclear microsatellites; Orchidaceae